1970
DOI: 10.1017/s0033822200008286
|View full text |Cite
|
Sign up to set email alerts
|

University of Pennsylvania Radiocarbon Dates XIII

Abstract: This date list includes those series of samples completed in this laboratory as of November 1969. The b.p. ages are based upon a.d. 1950, and are calculated with a half-life value of 5568 yr. All samples were counted at least twice for periods of not less than 1000 minutes each. Errors quoted are derived from measurement of samples, background, and modern-age calibration, but do not include any half-life error. All samples were pretreated with 3N HCl, and some, where noted, were given additional pretreatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Defining an absolute chronology for Ganj Dareh has proved a vexing issue since it was first discovered, due to what appear to be stratigraphic inversions, incoherent age ranges, unclear sample selection and position and occasional large discrepancies in reported ages. The various dates obtained prior to 2000 suggested an occupation span of up to 2300 radiocarbon years, although there was also no clear relationship between sample depth and age [34][35][36][37]. Recently, a battery of AMS radiocarbon dates on goat and human remains have apparently largely resolved the issue [8,38].…”
Section: Chronologymentioning
confidence: 99%
See 1 more Smart Citation
“…Defining an absolute chronology for Ganj Dareh has proved a vexing issue since it was first discovered, due to what appear to be stratigraphic inversions, incoherent age ranges, unclear sample selection and position and occasional large discrepancies in reported ages. The various dates obtained prior to 2000 suggested an occupation span of up to 2300 radiocarbon years, although there was also no clear relationship between sample depth and age [34][35][36][37]. Recently, a battery of AMS radiocarbon dates on goat and human remains have apparently largely resolved the issue [8,38].…”
Section: Chronologymentioning
confidence: 99%
“…Two charcoal samples collected in 1965 yielded age ranges of 10,400 ± 150 BP (GaK-807) and 8910 ± 170 BP (GaK-994), which were later correlated to Levels E and D, respectively [ 34 ]. This indicated that the site may have been occupied as early as the 10 th Millennium BC, although all subsequent dates commissioned by Smith indicated occupations constrained to the 8 th or 7 th Millennium [ 35 37 ]. More recently, dates on collagen from goat remains [ 8 ] and on collagen from human remains [ 38 ] have also indicated that the GaK-807 date is aberrant, and constrain the accumulation of the site’s five levels to a 200–300 year span after about 10,100 cal BP.…”
Section: Introductionmentioning
confidence: 99%
“…Excavated by Univ Mus, 1958Mus, , 1959Mus, , 1961Mus, , and 1968. Samples coil 1968; subm by R H Dyson, Jr, Univ 1\f us, Univ Pennsylvania, Philadelphia (1965Lawn, 1970;Ralph, 1959;Stuckenrath, 1963;Stuckenrath et al, 1966).…”
Section: P Near East 1 Iran Hajji Firuz Tepe Seriesmentioning
confidence: 99%
“…However, the flint tools and animal figurines are not unlike those in succeeding levels. Radiocarbon dates for the upper levels of the site are as follows (Kigoshi 1967;Lawn 1970 Level D was partially destroyed by fire, an accident that has preserved two of the most interesting features of the site. The first is the presence of surprisingly sophisticated forms of solid architecture employing long 'plano-convex' bricks; the second, the existence of simple pottery, perhaps originally lightly fired, which is to be dated before 7000 be and is the oldest so far known in the Middle East.…”
Section: Ganj Dareh Tepementioning
confidence: 99%